Draft Ninth Plan 1997-2002 and Annual Plan 1997-98 Tribal Sub Plan and Special Component Plan Government of Karnataka - Planning Commission (Planning Commission, 1997)
Draft Ninth Plan 1997-2002 Annual Plan 1997-98 Tribal Sub Plan and Special Component Plan Government of Karnataka Crop Husbandry Soil & Water Conservation Food Storage and Water Housing.
Government of Karnataka
Department of Social Welfare
Keywords: Government of Karnataka; Crop Husbandry; Soil & Water Conservation; Food Storage and Water Housing; Investment in Agricultural Financial Interest; Other Agricultural Programme Marketing & Quality Control; Cooperation; Jail Buildings; Stationery & Printing; Administrative Buildings; Other Administrative Services; Secretariat Economic Services.